If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 28 + -9x + 21 = 6x + -6 Reorder the terms: 28 + 21 + 4x + -9x = 6x + -6 Combine like terms: 28 + 21 = 49 49 + 4x + -9x = 6x + -6 Combine like terms: 4x + -9x = -5x 49 + -5x = 6x + -6 Reorder the terms: 49 + -5x = -6 + 6x Solving 49 + -5x = -6 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 49 + -5x + -6x = -6 + 6x + -6x Combine like terms: -5x + -6x = -11x 49 + -11x = -6 + 6x + -6x Combine like terms: 6x + -6x = 0 49 + -11x = -6 + 0 49 + -11x = -6 Add '-49' to each side of the equation. 49 + -49 + -11x = -6 + -49 Combine like terms: 49 + -49 = 0 0 + -11x = -6 + -49 -11x = -6 + -49 Combine like terms: -6 + -49 = -55 -11x = -55 Divide each side by '-11'. x = 5 Simplifying x = 5
| 2(x-4)=x+19 | | 40=68-7x | | -2+4(-8y+2)=-7(9y+1)-1 | | 60=68-7x | | -f^2-3t=0 | | 3y+x+4y+x-5=180 | | 1.2x-4.2=3.3 | | 3.4x-2=6.8 | | 5+x=33 | | 2(3x+1)+6=5(-2x-8) | | 2x-2-1=0 | | 2.32x=-46.73 | | 5x+9-8(x+1)=6X+5 | | 12x+6x= | | 1.8x+5.2=-3.5x-0.1 | | -3v-4=2v-19 | | x-(-24.82)=-71.94 | | 10-(2,5.4-3,8)= | | 12x+6x=18 | | 120x^2-8x-16=0 | | 6g+4(-8+5g)=1-g | | 81+x=33 | | 3m^3+24= | | f(-4)=16+3(-4)-7 | | x-29.65=-90.34 | | f(5)=2(25)+3(5)-4 | | c=kry | | 2x+6-3y=-12 | | r^3(c^3-125)+125(c^3-125)= | | 3.81x=69.24 | | 1.5p=1.23p+8 | | -41x=82 |